The Relationship Of The Physical Environment Of The House With The Event Of Diarrhea In Children In Pass, Sarudik District, Tapanuli Central Regency - Devi Kristina Hutagalung; Piuskosmas Fau (Science Midwifery, 2019)
The condition of the house and the environment that does not meet health requirements is a risk factor for the transmission of various diseases, especially environmental-based diseases. The physical environment of the house that does not meet the requirements is a risk factor. Poor home sanitation can cause toddlers to get diarrhea. This study aims to determine the relationship between the physical environment of the house and the incidence of diarrhea in the sand in the Sarudik sub-district, Tapanuli district in 2019. The sample is 135 households. The instrument is a demographic data questionnaire. The Chi Square test shows that there is a relationship between the physical environment and the incidence of diarrhea. Increased public knowledge in the field of environmental health, especially regarding the sanitation of the residential environment (PLP)/house sanitation.